2020
DOI: 10.1093/mnras/staa275
|View full text |Cite
|
Sign up to set email alerts
|

The connection between the UV/optical and X-ray emission in the neutron star low-mass X-ray binary Aql X-1

Abstract: Accreting neutron stars and black holes in low-mass X-ray binaries (LMXBs) radiate across the electromagnetic spectrum. Linking the emission produced at different wavelengths can provide valuable information about the accretion process and any associated outflows. In this work, we study simultaneous X-ray and UV/optical observations of the neutron star LMXB Aql X-1, obtained with the Neil Gehrels Swift Observatory during its 2013, 2014 and 2016 accretion outbursts. We find that the UV/optical and X-ray emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…About one-third of low-mass X-ray binaries (LMXBs) hosting neutron stars (NSs) are transient sources and characterized by a luminosity that varies over ∼10 32 -10 38 erg −2 s −1 , which is likely caused by an instability of the accretion induced by a variable accretion rate,  M. In this picture, the accretion flow drained from the companion star propagates toward the NS from the outer regions of the accretion disk (for a review see, e.g., Done et al 2007), which is confirmed by multiwavelength observations (e.g., López-Navas et al 2020). Except for the accretion rate, the NS's parameters, e.g., magnetic field and spin period, could also affect the accretion process.…”
Section: Introductionmentioning
confidence: 83%
“…About one-third of low-mass X-ray binaries (LMXBs) hosting neutron stars (NSs) are transient sources and characterized by a luminosity that varies over ∼10 32 -10 38 erg −2 s −1 , which is likely caused by an instability of the accretion induced by a variable accretion rate,  M. In this picture, the accretion flow drained from the companion star propagates toward the NS from the outer regions of the accretion disk (for a review see, e.g., Done et al 2007), which is confirmed by multiwavelength observations (e.g., López-Navas et al 2020). Except for the accretion rate, the NS's parameters, e.g., magnetic field and spin period, could also affect the accretion process.…”
Section: Introductionmentioning
confidence: 83%
“…In previous correlation studies, the X-ray flux between 2 and 10 keV bands was usually calculated (e.g. Russell et al 2006 ;Armas Padilla et al 2013 ;Shahbaz et al 2015 ;L ópez-Navas et al 2020 ;Yao et al 2020 ). In order to compare with previous work, we carry out the same procedure using the 2-10 keV X-ray flux.…”
Section: The X-ray and Uv/optical Flux Correlationsmentioning
confidence: 99%
“…Flux calibration of the R1000B data was performed against ESO 2 and ING 3 Spectophotometric Standards (Oke 1974(Oke , 1990 depending on the epoch (Feige 66, Feige 110, G191-B2B, Ross 640 and G158-100) and using astrophy-photutils-based routines (Bradley et al 2019). We also applied a reddening correction of E B−V = 0.65 mag (López-Navas et al 2020). The main aim of this task is not to report absolute flux measurements but to compute line intensity ratios.…”
Section: Data Reductionmentioning
confidence: 99%